PERBEDAAN POLA RUGAE PALATAL ANTARA LAKI-LAKI DAN PEREMPUAN SUKU MINANG - Dhira Pratiwi; Dedi Sumantri; Nur Indrawati Lipoeto (Faculty of Dentistry Universitas Andalas, 2016)
Indonesia as a disaster-prone area allowed casualty in large numbers and need immediate identification. One way to identify it was the use forensic odontology. Palatal rugae pattern has been suggested as an alternative method in forensic odontology to determine gender in all sorts of ethnic and population. The aim of this study was to know the difference of palatal rugae pattern between males and females in Minang ethnic. This study used descriptive analytics with cross sectional approach. The study sample compromised 122 dental stone casts of Minang ethnic, 61 males and 61 females wih range 15-19 years. The method rugae identification was based classification of Thomas and Kotze. The data were analyzed by Mann-Whitney test. The most predominant palatal rugae pattern in Minang ethnic are wavy and primary rugae. The Minang males were predominantly wavy, followed by straight, curve, unification, and circular. The Minang females were predominantly wavy, followed by curve, straight, and unification. There was a significant (p<0,05) sex difference in the circular type which was higher in males. Palatal rugae pattern can be used as adjunct to sex differentiation between males and females of ethnic Minang in forensic odontology. Key words : Forensic odontology, analysis of rugae palatal, gender, Minang ethnic